Sampling and analysis of iron, steel and other ferrous metals. Methods of analysis. Determination of cobalt. Steel, irons and steelmaking materials: spectrophotometric method for trace amounts Part 3.11.2, (20th December 1991) - British Standards Institution,
No abstract available